Analysis of the Effect of Land Use Planning and Land Value in Gamping Subdistrict, Sleman, D.I Yogyakarta from 2013 to 2018 - Tasya Vuji Al-Vatia Vuji Al-Vatia; Prijono Nugroho Djojomartono (Jurnal Geospasial Indonesia, 2019)
ABSTRACT. Government policy is one of the factors that can affect land value in an area. One of the government policies is the determination of land use planning in the Regional Spatial Planning (RTRW) and Detailed Spatial Planning (RDTR) which are arranged by considering suitability, harmony, and balance of cultivation and protection functions, time, technology, socio-cultural and defense security function. This research aims to find out and prove the relationship between the land value and the effect of land use planning on land value in Gamping District, Sleman, D.I Yogyakarta. In this research used land trade transactions in 2013, 2014, 2015, 2016, 2017and 2018 that obtained from the ATR / BPN office of Sleman Regency. These datas are then corrected by adjusting the data type and time correction. The results of the correction are used to form a land value model. Modeling land values was developed by using multiple linear regression analysis with independent variables such as land use planning (RPL), land use (PL), distance to main road (JJU), distance to housing (JPR), distance to downtown (JPK), distance to campus (JKM), field’s wide (LB), distance to the district government center (JPB), and distance to subdistrict government center (JPC). Evaluation model use determination test (R2), t table test and the result of the evaluation model are tested with Coefficient of Variation (COV). From these six years, only in 2013, 2014, 2016 and 2017 land value modeling could be modeled.  From the result of research, it is known that the land use planning effect the land value. But only significantly affected in 2016. This indicates that the land use planning has little effect on land value.